2017
DOI: 10.1007/s00464-017-5658-y
|View full text |Cite
|
Sign up to set email alerts
|

Single-incision laparoscopic common bile duct exploration in 101 consecutive patients: choledochotomy, transcystic, and transfistulous approaches

Abstract: LCBDE with a 100% ductal clearance rate is possible following an algorithm for various approaches. SILCBDE is feasible under a low threshold for procedure conversion. A transcystic approach should be tried first if indicated, and a longitudinal cystic ductotomy to the cystocholedochal junction is beneficial. Prospective, randomized trials comparing single-incision and multi-incision LCBDE are anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Furthermore, Chuang et al described a novel LESS transfistulous bile duct exploration and stone removal without drainage for Mirizzi syndrome type II with 80% success rate [73]. Supporting previous results and adding more evidence to the safety of the technique, the same authors reported 101 consecutive cases of successful LESS CBD exploration and concluded that in experienced hands, the procedure is feasible and a safe option for treatment of complicated and noncomplicated choledocholithiasis under low threshold for conversion [74].…”
Section: Less Common Bile Duct Explorationmentioning
confidence: 85%
“…Furthermore, Chuang et al described a novel LESS transfistulous bile duct exploration and stone removal without drainage for Mirizzi syndrome type II with 80% success rate [73]. Supporting previous results and adding more evidence to the safety of the technique, the same authors reported 101 consecutive cases of successful LESS CBD exploration and concluded that in experienced hands, the procedure is feasible and a safe option for treatment of complicated and noncomplicated choledocholithiasis under low threshold for conversion [74].…”
Section: Less Common Bile Duct Explorationmentioning
confidence: 85%
“…The single-incision LCBDE (SILCBDE) technique has been described in detail previously[ 22 , 23 ]. The patient was given general anesthesia and placed in the reverse Trendelenburg position.…”
Section: Literature Review and Our Own Experiencementioning
confidence: 99%
“…Compared with the difficulty in LCBDE for SI patients, SILCBDE seems to have some advantages. We developed this novel technique in July 2012, and it soon became our standard of care for choledocholithiasis, including difficult situations such as Mirizzi syndrome Csendes type II-IV[ 22 , 23 , 60 ]. In addition to a 5-mm 50-cm-long 30-degree laparoscope and a 5-mm flexible fiber choledochosope set, only conventional straight laparoscopic instruments were needed.…”
Section: Laparoscopic Common Bile Duct Exploration In Situs Inversus ...mentioning
confidence: 99%
“…The clinical outcomes compare favorably with published studies (Table 6). [41][42][43][44][45][46][47][48] They encouraged our gastroenterologists to discontinue the on-site ERCP service 24 years ago. In addition, we prospectively measured important outcomes including the referral to surgery and presentation to resolution intervals and the number of episodes.…”
Section: Role Of Subspecialisation and Service Designmentioning
confidence: 99%